Perancangan Sistem Monitoring Konsultasi Bimbingan Akademik Mahasiswa dengan Notifikasi Realtime Berbasis SMS Gateway - Jumri, Jurista Purnama (JUSTIN (Jurnal Sistem dan Teknologi Informasi), 2013)
Guidance, consultancy and discussionbetween students and lecturer are an activity thatsupports the smooth and effective learning process in university, and also facilitate the process of re-listsemester. Therefore, an online web-basedmonitoring system with real time notification isdesigned. This system aims is allowing students andlecturer to consult, facilitating students to designcourses to be taken in the next half of the semesteron the re-registration process, and allowing all usersto access the system data on the system either viacomputer, mobile phone, iPad and othercommunication devices that support. In addition toweb-based communication services, this system alsorequired communication service to support thesystem efficiency by using SMS (Short MessageService) gateway feature. SMS gateway canperform transactions with database to send anotification message update of the system to allstudents and lecturers in real time.